1995
DOI: 10.1203/00006450-199508000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Metabolic Characterization of Ischemic Contracture in the Neonatal Pig Heart

Abstract: Isolated, paced, isovolumetrically beating piglet hearts ( n = 37) underwent retrograde aortic perfusion with a crystalloid solution during three periods: 1) baseline (coronary perfusion pressure 60 mm Hg), 2) ischemia (coronary flow 10% of baseline for -80 min), and 3) reperfusion (perfusion pressure returned to baseline). In one group of hearts, glycolysis (using "H,o formation from [3H]glucose) was assessed. During baseline, peak systolic pressure (PSP) was 101.1 i 5.0 mm Hg, end diastolic pressure (EDP) 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Therefore, baseline oxygen delivery in these experiments was adequate, as evidenced by normal and sustained LV pressure development, without the hearts requiring complete extraction of coronary arterial oxygen. We have previously shown that piglet hearts perfused with this preparation are functionally stable for at least 90 min, the time period required for the proposed experiments [11,14].…”
Section: Experimental Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, baseline oxygen delivery in these experiments was adequate, as evidenced by normal and sustained LV pressure development, without the hearts requiring complete extraction of coronary arterial oxygen. We have previously shown that piglet hearts perfused with this preparation are functionally stable for at least 90 min, the time period required for the proposed experiments [11,14].…”
Section: Experimental Designmentioning
confidence: 99%
“…Any fluid within the ventricular chamber, e.g., from Thebesian circulation, was vented through an "1-mm apical stab wound. This maneuver reduces the possibility that a fluid collection around the balloon could after EDP [11]. The coronary flow was measured by timed collections of the pulmonary artery (coronary venous) effluent.…”
Section: Mechanical Function and Coronary Flowmentioning
confidence: 99%
See 3 more Smart Citations